Assessing crown reduction as a strategy to mitigate drought stress during initial development of sessile oak and Norway spruce saplings - Arsić Janko; Stojanović Marko; Horáček Petr; Mikhailov Sergei; Krejza Jan (Central European Forestry Journal)
Droughts, amplified by climate change, pose a significant threat to the success of both artificially and naturally regenerated forests. Understanding how these changes affect the initial stages of saplings development is crucial for forest establishment, particularly for ecologically and economically important species like Norway spruce and sessile oak in Central Europe. This study investigated the impact of crown reduction (CR) by 50% of crown length on saplings of each species. Automatic dendrometers were installed on 24 saplings per species to precisely monitor growth and water-related stem changes. The main objective was to investigate the potential ameliorative effect of CR on water-stressed saplings during their initial development. Our study hypothesized that CR, by decreasing leaf area and consequently water use, would improve water availability and facilitate sapling growth. The results indicate that CR may enhance soil water availability thereby supporting the growth of water-stressed Norway spruce saplings but not those of sessile oak. The tree water deficit – an indicator of tree water status – significantly improves in Norway spruce saplings subjected to CR (p < 0.05). Conversely, this treatment resulted in the depletion of stem water status in sessile oak saplings. The species-specific growth phenology revealed that CR led to an increase in the number of growing days for Norway spruce compared to sessile oak saplings. In summary, CR may be considered a beneficial method for alleviating stress in Norway spruce saplings, especially during drought. In addition, further testing in field conditions is necessary to confirm these results.